Pott’s Puffy tumor and intracranial complication developing secondary to acute frontal sinusitis: A case report Akut frontal sinüzite bağlı gelişen pott’s puffy tümör ve intrakraniyal enfeksiyon: Olgu sunumu - ÖZTANIR, MUSTAFA NAMIK; BAYINDIR, TUBA; Fırat, Çiğdem; Özerk, Ali; ÖZDEMİR, ZEYNEP; Öztanır, Namık (My University, 2016)
Aim: The aim of this study was to compare the lifestyle behaviors of women with and without stress urinary incontinence (SUI), and to investigate the effects of lifestyle behaviors on SUI. Materials and Methods: The study included 30 women who were diagnosed with SUI, 25-50 years old, who agreed to participate in the study voluntarily and 30 healthy women who met our study criteria with a total of 60 women. The data were evaluated using a questionnaire including demographic information and urinary incontinence risk factors of the women prepared by the researcher, and healthy lifestyle behaviors by Healthy Lifestyle Behavior Scale-II (HLBS-II), SUI by International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF). Results: When the HLBS-II scores of the groups were examined, it was observed that the scores of the group with SUI were lower and a statistically significant difference was found between the groups (p<0.005). There was a negative statistically significant relationship between the total score HLBS-II and total score ICIQ-SF (p=0.026). Discussion: As a result, healthy lifestyle behaviors are associated with SUI, and will affect the lifestyle positively.